Svp26 Facilitates Endoplasmic Reticulum to Golgi Transport of a Set of Mannosyltransferases in Saccharomyces cerevisiae - Noda, Yoichi (American Society for Biochemistry and Molecular Biology, 2010)
Svp26 is a polytopic integral membrane protein found in the ER and early Golgi compartment. In the Δsvp26 cell, the Golgi mannosyltransferase Ktr3 remains in the ER. Here, we report that two other Golgi mannosyltransferases, Mnn2 and Mnn5 are also mislocalized and found in the ER in the absence of Svp26 and that localization of other mannosyltransferases including Mnn1 are not affected. Mnn2 and Mnn5 bind to Svp26 in vivo as Ktr3 does. Using an in vitro budding assay, the incorporation of Ktr3 and Mnn2 in the COPII vesicles is greatly stimulated by the presence of Svp26. As Svp26 itself is an efficient cargo, Svp26 is likely to support selective incorporation of a set of mannosyltransferases into COPII vesicles by working as their adaptor protein. The domain switching between Svp26-dependent Mnn2 or Ktr3 and Svp26-independent Mnn1 suggests that the lumenal domain of mannosyltransferases, but not the cytoplasmic or transmembrane domain, is responsible for recognition by Svp26.